Pendidikan sebagai Agen Transformasi Sosial dalam Pelestarian Nilai Budaya Lokal Suku Osing di Banyuwangi - Astuti, Erma Hari Tri; Khilmah, Khilmah; Mulyana, Asep; Udin, Tamsik (INCARE, International Journal of Educational Resources, 2025)
Education plays a strategic role in preserving local culture amidst the currents of modernization and globalization. This study aims to analyze the role of education in safeguarding the cultural values of the Osing ethnic group in Kemiren Village, Banyuwangi, which is recognized as a traditional village and cultural center of the Osing community. Kemiren Village utilizes local wisdom–based tourism as a medium to engage the community, particularly the younger generation, in maintaining cultural heritage. This research employs a descriptive qualitative approach with a case study in Kemiren Village, integrating formal, non-formal, and informal education in the processes of social transformation and cultural preservation. The findings reveal that education through cultural activities such as festivals, art performances, and traditional art training plays a vital role in transmitting Osing cultural values. Furthermore, the implementation of a local culture–based curriculum in schools strengthens cultural identity among the younger generation. Despite challenges posed by modernization and cultural commercialization, culture-based education in Kemiren has proven effective in sustaining and preserving Osing traditions. These findings affirm that education involving active community participation can serve as an agent of social change and reinforce social cohesion in the preservation of local culture.